Croup – the most important questions and answers - Sybilski, Adam J. (Paediatrics and Family Medicine, 2019)
Until the end of the first half of the 20th century croup was associated mainly with diphtheria caused by Corynebacterium diphtheriae. However, now the term “croup” covers a whole group of disorders of the larynx, trachea and bronchi. The term refers to a number of disorders included in ICD-10 and may be used as a synonym for acute laryngitis, laryngotracheitis and laryngotracheobronchitis. The group of diseases included under the term “croup” is particularly dangerous for children: due to specific anatomical and physiological features stridor may only occur when a child is crying or moving. The most common aetiological factors for acute laryngotracheitis are viruses (e.g. parainfluenza). Croup may also be caused by bacteria. Typical symptoms include stridor, cough (barking, seal-like), hoarseness and activation of accessory respiratory muscles. As the disease progresses, upper airway obstruction and laryngeal dyspnoea increase and the patient develops tachypnoea with a prolonged inspiratory phase. The child’s anxiety increases. The course of the disease and the ultimate level of airway obstruction may vary. The diagnosis of croup symptoms is based on physical examination and interview. Initially, the severity of symptoms should be assessed using the Westley score. Pharmacotherapy includes glucocorticoids (nebulised, oral, parenteral) and adrenaline (nebulised). In Poland, the first line therapy for croup is nebulised glucocorticoids. The oral and inhaled route of administration of glucocorticoids are equally recommended. In severe forms of croup oxygen may be administered.